Control of Gut Inflammation by Modulation of Purinergic Signaling - Vuerich, Marta; Mukherjee, Samiran; Robson, Simon C.; Longhi, Maria Serena (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD) is a serious inflammatory condition of the gastrointestinal tract. Crohn’s disease (CD) and ulcerative colitis (UC) are two of the most common IBD manifestations and are both associated with unfettered inflammation, often refractory to conventional immunosuppressive treatment. In both conditions, imbalance between effector and regulatory cell immune responses has been documented and is thought to contribute to disease pathogenesis. Purinergic signaling is a known modulator of systemic and local inflammation and growing evidences point to extracellular ATP/adenosine imbalance as a key determinant factor in IBD-associated immune dysregulation. In vitro and pre-clinical studies suggest a role for both ATP (P2) and adenosine (P1) receptors in dictating onset and severity of the disease. Moreover, our experimental data indicate ENTPD1/CD39 and CD73 ectoenzymes as pivotal modulators of intestinal inflammation, with clear translational importance. Here we will provide an updated overview of the current knowledge on the role of the purinergic signaling in modulating immune responses in IBD. We will also review and discuss the most promising findings supporting the use of purinergic-based therapies to correct immune dysregulation in CD and UC.